A Versatile Orthotopic Nude Mouse Model for Study of Esophageal Squamous Cell Carcinoma. (5th March 2015) - Ip, Joseph Chok Yan; Ko, Josephine Mun Yee; Yu, Valen Zhuoyou; Chan, Kwok Wah; Lam, Alfred K.; Law, Simon; Tong, Daniel King Hung; Lung, Maria Li
Abstract : Increasing evidence indicates tumor-stromal interactions play a crucial role in cancer. An in vivo esophageal squamous cell carcinoma (ESCC) orthotopic animal model was developed with bioluminescence imaging established with a real-time monitoring platform for functional and signaling investigation of tumor-stromal interactions. The model was produced by injection of luciferase-labelled ESCC cells into the intraesophageal wall of nude mice. Histological examination indicates this orthotopic model is highly reproducible with 100% tumorigenesis among the four ESCC cell lines tested. This new model recapitulates many clinical and pathological properties of human ESCC, including esophageal luminal stricture by squamous cell carcinoma with nodular tumor growth, adventitia invasion, lymphovascular invasion, and perineural infiltration. It was tested using an AKT shRNA knockdown of ESCC cell lines and the in vivo tumor suppressive effects of AKT knockdown were observed. In conclusion, this ESCC orthotopic mouse model allows investigation of gene functions of cancer cells in a more natural tumor microenvironment and has advantages over previous established models. It provides a versatile platform with potential application for metastasis and therapeutic regimen testing.